Revenue Administration : Managing the Shadow Economy - Russell, Barrie (Technical Notes and Manuals; Technical Notes and Manuals ;, 2010)
This technical note focuses on the concept of a shadow economy and explains its main characteristics. Although a shadow economy is acknowledged by all G-20 countries as a major and enduring revenue risk, by its nature the size of a shadow economy is difficult to measure. Sweden, however, estimates that at least half of its total tax gap is attributable to a shadow economy. This note explains what action should revenue agencies take to manage a shadow economy. The most recent initiatives to manage a shadow economy are also described.